Manajemen Layanan Akademik Di MA Darul ‘Ulum Ath-Thahiriyah Paladang Kab. Pinrang - Fadilah, Nurul; Uswatun Hasanah; Muhammad Alwi (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze the management of academic services at Madrasah Aliyah Darul 'Ulum Ath-Thahiriyah, Paladang, Pinrang Regency. Using a qualitative approach through interviews, observation, and documentation, this study assesses important aspects of academic service management, such as the importance of academic services, their influence on academic achievement, collaboration between related parties, and evaluations. The results show that academic service management at this madrasah includes curriculum planning in accordance with Islamic values, the development of innovative teaching methods, and monitoring student learning progress. Effective academic services can improve the quality of education at the madrasah by supporting student character development..